Exploring the influencing factors of non-insulin drug prescriptions in discharged patients with type 1 diabetes - Cheng, Yikang; Li, Haizhen; Liu, Xin; Jin, Xiaolong; Han, Junming; Du, Jing; Xu, Chao (Frontiers in Endocrinology, 2024)
Objective: Evaluate the admission indicators and characteristics of individuals diagnosed with Type 1 Diabetes (T1D) to ascertain potential impact on the choice of glucose control therapy after discharge. Methods: A total of 398 eligible T1D patients were selected. We conducted multivariable logistic regression analysis to determine the independent influence of predictors on the selection of glucose control therapy after discharge. To explore the influencing factors of different subgroups, we additionally performed subgroup analyses based on gender and age. Results: Our study revealed that body mass index (BMI) was noteworthy influence factor for prescription of insulin and non-insulin antidiabetic drug (NIAD prescription) in T1D patients of general population [OR=1.213(1.092,1.354), p<0.001], male [OR=1.213(1.038−1.438), p=0.019], female [OR=1.194(1.024−1.412), p=0.030] and individuals below the age of 30 years [OR=1.146(1.020−1.301), p=0.028]. Diastolic blood pressure (DBP) was a protective factor for NIAD prescription in the general population [OR=0.961(0.931,0.990), p=0.009] and women [OR=0.926(0.875−0.975), p=0.005]. The other risk factors of NIAD prescription in male were dyslipidemia [OR=6.415(1.470−46.350), p=0.028]. Pulse pressure [OR=1.036(1.007−1.068), p=0.016] constitutes an additional risk factor of NIAD prescription among individuals below the age of 30 years. The risk factors of NIAD prescription for people aged 30 to 50 years are length of stay [OR=1.097(1.014−1.196), p=0.026] and initial blood glucose [OR=1.078(1.007−1.168), p=0.047]. In the case of individuals aged above 50 years, physicians exhibited a higher tendency to prescribe supplementary non-insulin medications to males [OR=9.385(1.501−87.789), p=0.029]. Conclusions: We identified notable factors that influence discharge prescriptions in patients with type 1 diabetes. In order to enhance the treatment outcome for the patient, clinicians ought to have a special focus on these indicators or factors.